Care workers' voices in designing assistive technologies for preventing malnutrition in older people with dementia: Innovative Practice. (February 2020) - Jayatilaka, Asangi; Ranasinghe, Damith C; Falkner, Katrina; Visvanathan, Renuka; Wilson, Anne
Technology may be considered a way to promote nutritional health in people with dementia living in their home. For technologies to be effective and accepted by users, understanding technological needs prior to technology development is crucial; however, this necessitates greater research investment. Consequently, our focus is to derive needs for nutritional health promoting technologies for older people with dementia by understanding perceptions of care workers recruited by the aged care industry. In this paper, we provide a brief description of the theoretical framework that underpins the research study and the research methods selected. Significant learning outcomes related to the research methods include managing hierarchical relationships among participants, engagement with the care workers working in the community and using external material to spark discussion.